2022
DOI: 10.21203/rs.3.rs-2232367/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The red seaweed Asparagopsis taxiformis genome and integrative -omics analysis

Abstract: Seaweeds (marine macroalgae) are crucial to the functioning of healthy coastal ecosystems and global biogeochemical cycles, and sometimes provide novel solutions to help mitigate climate change. The red seaweed Asparagopsis taxiformis (Bonnemaisoniaceae, Rhodophyta) produces bioactive natural products that, when fed to cattle and sheep, can eradicate methane emissions from these livestock. However, in order to cultivate enough A. taxiformis to have a meaningful impact on global greenhouse gas emissions, we nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…The Asparagopsis taxiformis (L6) genome contains 145 transcription factors (Zhao et al., 2022). In our study, several transcription factors were identified with male‐biased gene expression in the tips (e.g., EIN3‐binding F‐box protein 1, GATA transcription factor 24‐like, zinc finger protein).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The Asparagopsis taxiformis (L6) genome contains 145 transcription factors (Zhao et al., 2022). In our study, several transcription factors were identified with male‐biased gene expression in the tips (e.g., EIN3‐binding F‐box protein 1, GATA transcription factor 24‐like, zinc finger protein).…”
Section: Discussionmentioning
confidence: 99%
“…To gain insight into the mbb gene expression in Asparagopsis taxiformis , all mbb genes were obtained from the Asparagopsis genome (Zhao et al., 2022), and their gene expression was obtained from November 2019 female and male samples (including tip, main axis, and rhizome). Bar graphs showing relative gene expression of mbb genes were constructed utilizing Log2 TPM (transcripts per million) with error bars represented mean ± standard deviation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data collection for red algal assemblies returned 34 genome assemblies from the NCBI database, as well as an additional A. taxiformis SC genome that has since been published on NCBI (GCA_030407315.1) [25]. Searching for Chlorophyta returned 170 assemblies, of which 41 had protein annotations available.…”
Section: Data Collection and Functional Annotationmentioning
confidence: 99%